Examining gender differences in the access to and implementation of climate-smart agricultural practices in Central America - Acosta, Mariola; Bonilla Findji, Osana; Eitzinger, Anton; Arora, Diksha; Martínez Barón, Deissy; Bejarano, Gustavo; Suchini, Jose Gabriel (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This Info Note summarizes the findings from the monitoring efforts of CSA practices conducted in 2018 in the Climate-Smart Villages of Guatemala and Honduras within the framework of the project “Generating evidence on gender-sensitive climate-smart agriculture to inform policy in Central America” led by the International Center of Tropical Agriculture (CIAT), with the financial support of the International Development Research Center (IDRC).